2019
DOI: 10.1302/0301-620x.101b1.bjj-2018-0601.r2
|View full text |Cite
|
Sign up to set email alerts
|

Higher 30-day mortality associated with the use of intramedullary nails compared with sliding hip screws for the treatment of trochanteric hip fractures

Abstract: Aims The aim of this study was to investigate the association between the type of operation used to treat a trochanteric fracture of the hip and 30-day mortality. Patients and Methods Data on 82 990 patients from the National Hip Fracture Database were analyzed using generalized linear models with incremental case-mix adjustment for patient, non-surgical and surgical characteristics, and socioeconomic factors. Results The use of short and long intramedullary nails was associated with an increase in 30-day mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 30 publications
7
39
2
1
Order By: Relevance
“…Additionally, four studies 7 , 35 , 42 , 47 reported an increased mortality with intramedullary fixation, as shown in our results (RR 1.33, p = 0.04) in patients with COVID-19 infection. The obvious difference between this type of implant and other forms of extracapsular fixation is the instrumentation of the femoral canal which is known to be associated with increased mortality due to increased intramedullary pressure, embolic showers and fat extravasation and may be catastrophic to COVID-19 patients, representing a “second-hit” postulated by Lebrun et al and Egol et al 39 , 42 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, four studies 7 , 35 , 42 , 47 reported an increased mortality with intramedullary fixation, as shown in our results (RR 1.33, p = 0.04) in patients with COVID-19 infection. The obvious difference between this type of implant and other forms of extracapsular fixation is the instrumentation of the femoral canal which is known to be associated with increased mortality due to increased intramedullary pressure, embolic showers and fat extravasation and may be catastrophic to COVID-19 patients, representing a “second-hit” postulated by Lebrun et al and Egol et al 39 , 42 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the A1/2 intertrochanteric proximal femoral fractures, the SHS construct remains the implant of choice for various reasons, including lower cost and decreased mortality compared with cephalomedullary devices based on the NHFD [ 9 - 10 ]. We have demonstrated the importance of intraoperative screw placement besides presenting technical tips to improve this.…”
Section: Discussionmentioning
confidence: 99%
“…1 Impacto da fratura na QV 1, 2, 3, 5 e 7 2 Programa de prevenção de fraturas e QV 4, 6 e 10 3 Relação entre fatores intrínsecos para risco de fraturas e QV 8 e 9 Fonte: Dados da Pesquisa. outras pessoas e proporciona a melhora da QV do idoso (WHITEHOUSE et al, 2019).…”
Section: Categorias Artigosunclassified